A short-term clinical evaluation of immediate implant placement in periodontitis patients - Li, Guojiang; Chen, Xufeng; Feng, Yujia; Lu, Ying; Liao, Wanlin; Huang, Rui; Yang, Ejiao; Lai, Renfa; Feng, Zhiqiang (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundWith the advancement of oral implant technology, immediate implant placement is believed to be feasible for periodontitis patients. However, there is a lack of high-quality clinical studies regarding this approach. This study aimed to observe the short-term implant survival rate and conditions of peri-implant tissues in periodontitis patients who received immediate implants without systematic periodontal treatment.MethodsThis retrospective study included 95 patients and 234 implants treated at the Stomatological Hospital of Jinan University from June 2017 to December 2022. Patients were classified according to the 2018 AAP/EFP periodontal classification system, with Stage determined by CBCT-assessed marginal bone loss (MBL) and Grade estimated based on annual bone loss rate, smoking status, and diabetes history. Immediate implant placement was performed following atraumatic tooth extraction, with bone defects augmented using Bio-Oss bone graft and covered with Bio-Gide collagen membrane as needed. Patients were followed up for 12 months, during which implant survival, modified sulcus bleeding index (mSBI), modified plaque index (mPLI), marginal bone loss (MBL), and peri-implant probing depth (PPD) were assessed.ResultsA total of 95 patients (234 implants) were included, with a mean age of 58.59 years. The distribution of Stage II-IV and Grade A-C periodontitis was recorded. Preoperative assessments showed a significant increase in P-PDD, CAL, and MBL with greater disease severity (p < 0.001). One-year follow-up data indicated an implant survival rate of 97.86%, with Kaplan-Meier survival analysis revealing significantly lower survival rates in Stage IV and Grade C patients (p < 0.05). Postoperative soft tissue health assessment showed significant differences in mSBI and mPLI between stages (p = 0.002, p = 0.007) but not grades (p > 0.05). PPD did not differ significantly among groups (p > 0.05), whereas MBL was significantly higher in Stage IV than in Stage II and III (p < 0.001), though no significant differences were observed across grades (p > 0.05). Clinical and radiographic evaluations demonstrated favorable implant outcomes, with most patients reporting high satisfaction. These findings reinforce the viability of immediate implant placement in periodontitis patients, demonstrating high short-term success rates across different disease severities. While disease severity and progression rate may influence clinical outcomes, appropriate case selection, meticulous surgical techniques, and comprehensive postoperative care can lead to predictable and favorable implant success, even in patients with periodontitis.